Acute kidney injury and renal replacement therapy: terminology standardization - Reis,Thiago (2022)
Abstract The Department of Acute Kidney Injury (IRA) of the Brazilian Society of Nephrology prepared this document for the purpose of standardizing AKI terminology and dialysis modalities in the Portuguese language for Brazil. Several terms with similar meanings have been used in AKI and its dialysis modalities, causing confusion and disparities among patients, nephrologists, health institutions, private care companies, insurance companies and government entities. These disparities can impact medical care, hospital organization and care, as well as the funding and reimbursement of AKI-related procedures. Thus, consensual nomenclature and definitions were developed, including the definitions of AKI, acute kidney disease (AKD) and chronic kidney disease (CKD). Additionally, we addressed all dialysis modalities and extracorporeal procedures related to AKI, currently approved and available in the country. The Brazilian Society of Nephrology hopes that this Consensus can standardize the terminology and provide technical support to all involved in AKI care in Brazil.